The Analysis of Classroom Learning Activities Related to Students Multiple Intelligences in Drama Class - A Case Study - Jaufillaili, Jaufillaili; Farijanti, Dian (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
Drama is one of the lectures taught in English Education Department of UNSWAGATI. The classes at English Education department are categorized as big classes. Drama class demanded students to show their competence in any English skills, such as: listening, reading, writing and speaking. Drama could explore students’ multiple intelligences and it is an appropriate place to provide activities related to students’ multiple intelligences. Based on the explanation above, through this research, the writers had the aim to describe how is the students’ activity in drama class related to interactive domain of multiple intelligences based on McKenzie’s (2002), cited in Fauziati (2009: 112). Interactive domain of Multiple Intelligences consists of Linguistics domain, interpersonal domain and kinesthetic domain. Based on McKenzie’s (2002) cited in Fauziati (2009: 112), the learning activities in drama class are classified into three kinds of interactive domains, namely: linguistics, interpersonal and  kinesthetic. The result showed why such learning activities in drama class are classified into each domain because they fullfil the characteristics of each intelligence. Linguistics deals with words and language, interpersonal deals with other people’s feeling and kinesthetic deals with body movement control. Keywords: multiple intelligences, interactive domains, linguistics, interpersonal, kinesthetic, drama class